The importance of skill measurement for growth accounting - Øivind Anti Nilsen; Arvid Raknerud; Marina Rybalka; Terje Skjerpen (Institute for the Study of Labor (IZA), 2010)
In a growth accounting context one usually constructs a quality adjusted index of labor services by aggregating over predefined groups of workers, using the groups' relative wage bills as weights. In this article we suggest a method based on decomposing individual predicted wages into a skill-related part and a part unrelated to skill, where the former consists of both observed and unobserved components. The predicted wages, associated with individual skill attributes, are sorted and classified into deciles. The median predicted skill-related wage in each decile is used to construct an alternative skill-adjusted index of labor services. We find that Total Factor Productivity (TFP) growth decreases significantly when using the latter method. This means that when using the alternative method one explains more of the growth in labor productivity than what a more traditional labor quality adjustment procedure does.
Keywords: C23; D24; J24; J31; 330; TFP growth; skill measures; wage equation; Produktivität; Wirtschaftswachstum; Qualifikation; Messung; Lohnstruktur; Schätzung; Norwegen